PENGEMBANGAN MANAJEMEN PESERTA DIDIK MELALUI PROGRAM PENA IKK DI MI NU SUMPUT SIDOARJO - M. Athoiful Fanan; Anny Maesyaroh; Robiatus Solikhah (ICO EDUSHA, 2022)
This study discusses the development of learners' management through IK's pen program in MI NU Sumput Sidoarjo. The purpose of this study is to know the management of learners in MI NU Sumput Sidoarjo and the development of learners' management through the IKK pen program. This research uses descriptive qualitative approach. The data collection technique used is observation, interview and documentation. The results showed that MI NU Sumput implemented the management of the participants including the coaching of learners and development of learners. Development of Student Management through IKK Pen Program is a form of vision and missionary in implementing discipline attitude in classroom learning. The constraints or obstacles in the implementation of IK-sized II programs in MI NU Sumput are socialized miscellaneous, there are still students who are out without using queue numbers and use of queue numbers of outstanding classes are not used. Keywords: Development, Student Management, Ik Corpondence Pen Program References Ariska, Ria Sita. 2015. Manajemen Kesiswaan. Jurnal Manager Pendidikan. 9(6). Busyairi, A. dan Fani Oktavinati. 2019. Manajemen Peserta Didik Dalam Pengembangan Minat dan Bakat Melalui Kegiatan Ekstrakulikuler. Joyful Learning Journal. 8(4) Firdaus, Akmal dan Aslinda. 2020. Strategi Pengembangan Manajemen Peserta Didik Dalam Meningkatkan Mutu Pendidikan di MTsN Padang Panjang. Jurnal al-Fikrah VIII(2) Imron, Ali. 2015. Manajemen Peserta Didik Berbasis Sekolah, Jakarta: Bumi Aksara Jahari, Jaja dkk. 2018. Manajemen Peserta Didik. Jurnal ISEMA: Islamic Education Manajemen. 9(6) Khoirul Umam, Muhammad. 2018. Peningkatan Mutu Pendidikan Melalui Manajemen Peserta Didik. Jurnal al- Hikmah 6(2) Moleong, Lexy. 2004. Metodologi Penelitian Kualitatif. Bandung: Remaja Rosdakarya Mujahidin, Endin dkk. 2020. Pengembangan Manajemen Peserta Didik Program Tahfidz. Jurnal Ta’dhibuna: Jurnal Pendidikan Islam. 9(1) Nasihin dan Surani, 2009. Manajemen Peserta Didik. Bandung: Alfabeta Prihatin, 2011. Manajemen Peserta Didik. Bandung: Alfabeta Suwardi dan Daryanto, 2017. Manajemen Peserta Didik. Yogyakarta: Gaya Media